Climate information workshop - Kaffrine, Senegal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Putting climate forecasts into farmers' hands. The picture shows a training workshop for farmers on the interpretation and application of seasonal rainfall forecasts in our benchmark site Kaffrine, Senegal. This research is part of our work on Adaptation Through Managing Climate Risk.